2017
DOI: 10.1101/204933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns and Predictors of Tic Suppressibility in Youth with Tic Disorders

Abstract: Background: Tic suppression is the primary target of tic disorder treatment, but factors that

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…They can then provide an immediate contingent reward for successful tic suppression in the form of a token dispensed from the tic detector remotely, which can be exchanged for money at the end of the study. Many studies using the TST paradigm in children with tics have demonstrated that adding rewards for tic-free periods to verbal instruction to suppress tics yielded greater reduction in tics than verbal instruction alone [14,16,17,22,23]. Further, contingency of the reward was important, as tokens delivered noncontingently did not show similar benefit on tic reduction [24].…”
Section: Clinical Phenomenology Of Tic Suppressibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…They can then provide an immediate contingent reward for successful tic suppression in the form of a token dispensed from the tic detector remotely, which can be exchanged for money at the end of the study. Many studies using the TST paradigm in children with tics have demonstrated that adding rewards for tic-free periods to verbal instruction to suppress tics yielded greater reduction in tics than verbal instruction alone [14,16,17,22,23]. Further, contingency of the reward was important, as tokens delivered noncontingently did not show similar benefit on tic reduction [24].…”
Section: Clinical Phenomenology Of Tic Suppressibilitymentioning
confidence: 99%
“…With years of experience suppressing tics, patients with tics may become better at tic suppression over time. Tic suppressibility is observable in children younger than 10 years old, but is correlated with age and frequency of tics [23,26]. Still, somewhat surprisingly, children with recent onset of tics (i.e., within 6 months of tic onset) can suppress about 40% of their tics and do so more efficiently with immediate contingent reward [27].…”
Section: Clinical Phenomenology Of Tic Suppressibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Woods and Himle developed a tic suppression paradigm (TSP) that could be used in the experimental setting to demonstrate and quantify the effects of intentional tic suppression on tic rate in Tourette syndrome (TS) and other tic disorders 15 . In this paradigm, each participant is observed during several experimental conditions, baseline and differential reinforcement of zero-rate ticcing (DRO), and sometimes also verbal instruction to suppress tics and/or noncontingent reinforcement (NCR).…”
Section: Introductionmentioning
confidence: 99%